Survival in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Survival in the Sahel: an ecological and developmental challenge edited by Klaus Lesinger and Karin Schmitt and the International Service for National Agricultural Research (ISNAR) 1995 211pp ISBN 92 9118 020 3